Penerapan Asas Ultimum Remedium dalam Pemidanaan Tindak Pidana Pencucian Uang - Adhalia Septia Saputri; Lusia Sulastri (Journal of Mandalika Literature, 2025)
The principle of ultimum remedium is a principle in criminal law that places criminal sanctions as a last resort after other legal efforts are ineffective in enforcing the law. In the context of money laundering crimes, the application of this principle has an important role in maintaining a balance between effective law enforcement and the protection of human rights. This research aims to analyze the application of the ultimum remedium principle in the criminal offense of money laundering in Indonesia, as well as evaluate whether the criminal sanctions applied are in accordance with this principle. The research method used is a normative juridical approach with analysis of laws, regulations and court decisions related to money laundering crimes. The research results show that although the principle of ultimum remedium has been accommodated in criminal law theory in Indonesia, in practice there are often deviations in the imposition of criminal sanctions that are considered disproportionate. This research recommends strengthening the implementation of the ultimum remedium principle through clearer and more consistent legal policies, as well as increasing the capacity of law enforcement officials in applying it to money laundering cases.